Pola Kemampuan Literasi Digital Guru: Menelaah Kesenjangan Literasi Digital dari Perspektif Gender - Kharisma Salsabila, Chika; Wachidah, Kemil (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This research examines the digital literacy skills of elementary school teachers from a gender perspective, comparing male and female teachers in their implementation of digital literacy in learning activities at SD Muhammadiyah 1 Sidoarjo. SD Muhammadiyah 1 Sidoarjo has integrated digital technology into its learning activities, in line with its slogan, "Islamic and Digital School." This makes it an appropriate setting to investigate whether the educators possess the necessary digital literacy skills and effectively apply them in their teaching practices. The research employs a qualitative approach, producing descriptive data in the form of written or spoken words and observable behaviour using various natural methods. The study specifically focuses on the digital literacy skills of teachers from a gender perspective at SD Muhammadiyah 1 Sidoarjo. The findings indicate that the school's environment and classrooms are consistent with its vision, mission, and slogan of "Islamic and Digital School" in realizing and implementing digital education. Additionally, both male and female teachers demonstrate very good digital literacy skills. Based on data analysis from interviews and questionnaires, it can be concluded that the digital literacy skills of teachers, regardless of gender, fall into the "very good" category and align with the digital literacy indicators set by the Ministry of Communication and Information Technology (Kominfo). The final results of the study show that there is no gender bias in the digital literacy skills of teachers at SD Muhammadiyah 1 Sidoarjo.